Complainant emotional expressions and perceived credibility: exploring the role of perceivers' facial mimicry and empathy - Ask, Karl (Legal and criminological psychology, 2018)
Purpose. This research investigated the roles of perceivers’ facial mimicry and empathy in the emotional victim effect (EVE) – the finding that complainants tend to appear more credible when exhibiting (vs. not exhibiting) negative emotional displays during their statements. Because facial mimicry plays a key role in empathic responding, it was hypothesized that inhibiting and facilitating perceivers’ mimicry would attenuate and amplify the EVE, respectively. Methods. Participants (N = 362) in an experiment were instructed to mimic or not to mimic facial expressions (controls received no mimicry instructions) while watching a statement by an emotional or non-emotional rape complainant. Participants rated the complainant's believability and the extent to which they experienced cognitive and affective empathy. Results. The perceived believability of the complainant was not affected by complainant emotions, thus failing to replicate the EVE. However, the inhibition of mimicry unexpectedly reduced the perceived believability of the complainant, apparently by decreasing participants’ cognitive empathy. Conclusions. The current findings suggest that mimicry inhibition may increase scepticism in the context of credibility assessment. This has important implications for decision-making in legal settings and for research on the process of credibility attribution. Moreover, the failure to replicate the EVE adds to the cumulative evidence on the underlying effect size for the phenomenon.